2001
DOI: 10.1002/jbt.14
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of rat hepatic microsomal low molecular weight fatty acid ethyl ester synthase and its relationship to carboxylesterases

Abstract: We reported purification of a high molecular weight (HMW) (ca. 180 kD) and a low molecular weight (LMW) (ca. 60 kD) protein fractions from digitonized rat liver microsomes using ammonium sulfate precipitation followed by ion exchange and gel filtration column chromatography. Both fractions expressed fatty acid ethyl ester (FAEE) synthase as well as p-nitrophenyl acetate (PNPA)-hydrolyzing (esterase) activities. The HMW fraction was found to be a trimer with subunit molecular weight ca. 60 kD and structurally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…Similarly, other rat liver microsomal low molecular weight FAEE synthase were also found to have close structural and functional relationships to rat hepatic microsomal CEs [7]. Our recent studies on differential inhibition of FAEE synthase activity using trio-tolyl phosphate (␤-esterase inhibitor) in HepG2 and AR42J cells [6] and in vivo in rats [12] indicate that hepatic and pancreatic FAEE synthase are different.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, other rat liver microsomal low molecular weight FAEE synthase were also found to have close structural and functional relationships to rat hepatic microsomal CEs [7]. Our recent studies on differential inhibition of FAEE synthase activity using trio-tolyl phosphate (␤-esterase inhibitor) in HepG2 and AR42J cells [6] and in vivo in rats [12] indicate that hepatic and pancreatic FAEE synthase are different.…”
Section: Introductionmentioning
confidence: 93%
“…In the past 20 years, FAEE synthase has been purified and characterized from human and animal tissues, and it has been suggested that FAEE synthase is structurally and functionally different in the liver and pancreas [1,5,12]. It has also been shown that FAEE synthase is involved in the synthesis of fatty acid esters with other alcohols and amines [1,[4][5][6][7]16]. Surprisingly, pancreatic FAEE synthase activity is up-regulated following chronic ethanol exposure [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…FAEEs have also been associated with disease development in the alcoholic liver, heart, and pancreas ( 36,38,39 ). The molecular identities of enzymes that synthesize and degrade FAEEs are currently not established ( 40,41 ). It is thought that multiple hepatic microsomal carboxyesterases (CES) are able to catalyze the synthesis of FAEE; but because of this uncertainty, we did not exhaustively study expression of CES that might be involved in FAEE synthesis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular identities of enzymes that synthesize and degrade FAEEs are currently not established ( 40,41 ). It is thought that multiple hepatic microsomal carboxyesterases (CES) are able to catalyze the synthesis of FAEE; but because of this uncertainty, we did not exhaustively study expression of CES that might be involved in FAEE synthesis ( 41 ). Our results, however, identify ethyl oleate (C18:1) as the most abundant FAEE in the plasma and liver of alcohol-fed mice.…”
Section: Discussionmentioning
confidence: 99%